POTENTIAL MECHANISMS UNDERLYING THREAD EMBEDDING ACUPUNCTURE IN THE TREATMENT OF MUSCULOSKELETAL DISORDERS: A NARRATIVE REVIEW (Vietnam Journal of Community Medicine, 2026)
Background: Musculoskeletal disorders (MSDs) are a leading cause of disability worldwide. Thread embedding acupuncture (TEA) is an advanced modality evolved from traditional acupuncture, utilizing absorbable materials to maintain acupoint stimulation. However, the biological mechanisms underlying this method have not been summarized.Methods: This narrative review was conducted through a literature search on PubMed/MEDLINE, Scopus, Web of Science, and Google Scholar, including publications up to March 15, 2026. Evidence derived from cellular models, animal studies, clinical trials, and review articles concerning the mechanisms of TEA in MSDs and related biological pathways was screened and analyzed.Results: The mechanism of TEA operates through three distinct effect phases including the mechanical needling effect, the biochemical-immune response to the embedded material, and the maintenance of prolonged stimulation. This integration creates a specific acupoint microenvironment that acts as a stimulation depot, modulating anti-inflammatory cytokine networks, potentially disrupting the pathological cycle at myofascial trigger points, and supporting nerve regeneration. However, the majority of current evidence regarding these mechanisms is still based on animal models or extrapolated from the theoretical framework of traditional acupuncture.Conclusion: TEA exerts multi-layered therapeutic effects through the intersection of mechanical and biochemical factors. To firmly establish the independent physiological standing of this method, future research should focus on head-to-head trials comparing TEA with traditional acupuncture, evaluating differences among various thread materials, and acquiring direct evidence using objective human biomarkers.
Keywords: thread embedding acupuncture; acupuncture; musculoskeletal disorders; mechanism of action